Effects of Solvent/Solid Ratio and Temperature on the Kinetics of Vitamin C Extraction from Musa Acuminata - Khairul Anwar, Mohamad Said; Ibrahim, Yakub; Nurul Ain, Mohamed Alipah (JASPE, 2015)
This work studied on the kinetics of Vitamin C extraction from banana peel at different solvent/solid concentration and temperature. Musa Acuminata was ground into smaller sizes before contacted with methanol as a solvent in an ultrasonic bath. To study the effect of solvent/solid ratio, 4.5, 5.0 and 10.0 ml/g ratio were used for the extraction at fixed temperature. Then, the temperature was varied with the heating element available in the ultrasonic bath at 30, 45 and 60 oC, to study the effect of temperature on the extraction kinetics. It was found that high solvent/solid ratio (10 ml/g) provides more solute-solvent contact and prevents the extracted Vitamin C from coming into contact with the air. Besides, higher temperature (60 oC) contributes sufficient kinetic energy for Vitamin C distribution in the solvent which is important to prevent degradation with air. The best fitted kinetic model for Vitamin C extraction from Musa Acuminata is Ana et al. (2007) with equilibrium concentration of 0.05 g/L and 0.40 g/L.hr extraction rate